Identification and evaluation of antimicrobial and anti-arthritis activities of hydroethanolic extract of Rubus ellipticus leaves - Kumari, Anjana; Prakash, Vinit; Gupta, Dinesh; Kashyap, Lokender; Chopra, Hitesh; Gautam, Rupesh K.; Chakraborty, Sandip; Chandran, Deepak; Dhama, Kuldeep; Goyal, Rajat (Narra Sains Indonesia, 2023)
Rubus ellipticus is a native plant to India's tropical and subtropical regions and has been used as a traditional medicinal. The aim of the study was to identify and evaluate the antimicrobial and anti-arthritis activities of hydroethanolic extract of R. ellipticus leaves (HEERE). The leaves were collected from the Narkanda Valley, India and were shade-dried and finely ground to produce the powder. The hydroethanolic extract was utilized for phytochemical analysis to determine the existence of carbohydrate, phenolic, terpenoid, flavonoid, saponin, glycoside, tannin, protein, and alkaloid. The HEERE was further analyzed by gas chromatography-mass spectrometry (GC-MS) for the characterization of the phytoconstituents. The antimicrobial activity was tested against Escherichia coli, Staphylococcus aureus as well as Aspergillus niger. To assess its anti-arthritic activities, different doses of HEERE were given orally to complete Freund’s adjuvant (CFA)-induced albino Wistar rats for twenty-one days. The GC-MS analysis of hydroethanolic extracts from leaves detected and identified the presence of 33 phytochemical compounds. HEERE showed significant effects against E. coli, S. aureus, and A. niger strains at 600 ppm. Our data indicated that HEERE 200 mg/kg was more effective than 50 mg/kg as anti-arthritis. Paw volume, ankle-joint diameter, the number of leucocytes, and erythrocyte sedimentation rate (ESR) were all significantly reduced in experimental rats. Furthermore, when compared to respective standard drugs, the body weight, erythrocyte, hemoglobin, and synobium healing effect have all improved. These data demonstrated the potential of R. ellipticus for the long-term investigation of antimicrobial and anti-arthritic properties.